Optimization of extraction conditions of phytochemicals and antioxidant activity of Orthosiphon aristatus (Blume) Miq - Taokaenchan, Narin; Areesrisom, Pawinee; Areesrisom, Koblap; Sateinperakul, Sakchai (Health Science, Science and Technology Reviews, 2024)
The objective of this research was to investigate the optimal condition extraction of phytochemicals (phenolic and flavonoid contents) and antioxidant activity from Orthosiphon aristatus. The first experimental was studied the different extraction methods (maceration, ultrasonic, and microwave) and the ratio of ethanol and water (100:0, 80:20, 60:40, 40:60, 20:80, and 0:100) on yield of extraction, contents of total phenolic, and flavonoids. The experimental results showed that these two parameters affected the yield of extraction, total phenolic, and flavonoid contents. The optimum extraction conditions were using the ultrasonic method by extraction time with 30 mins and ethanol to water ratio (60:40 and 40:60) for the highest yield of extraction and total phenolic, furthermore, using ethanol to water ratio of 100:0 for flavonoid content. The second experimental was to determine the effect of single-factor by ultrasonic-assisted extraction. Three factors include extraction times (5-90 mins), the ratio of ethanol and water (100:0-0:100) and the sample weight (0.5-5.0 g). According to the analysis results, all single factors significantly affected phenolic, flavonoid content and antioxidant activity of Orthosiphon aristatus extract (p<0.05). The optimal an ultrasound-assisted extraction condition were followed: the extraction time was 70 min, the ethanol to water ratio of 80:20 and the sample weight with 5.0 g. Under these conditions, the phenolic, flavonoid content and antioxidant activity with 2, 2-diphenyl-1-picrylhydrazyl (DPPH) were 951.17 µg gallic acid equivalent (GAE)/mg extract, 2.42 mg quercetin equivalent (QE)/mg extract and IC50 of antioxidant value of 154.41 µg/mL, respectively.